2003
DOI: 10.53808/kus.2003.5.2.0321-l
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Characterization of Sundarbans Mangrove Forest of Bangladesh: On the Perspective of Aquatic Biodiversity

Abstract: The paper describes the characterization of water quality of Sundarbans Mangrove Forest of Bangladesh. Water samples of 28 stations, selected from the four major river systems of Sundarbans were collected. The sampling period was from January 2001 to July 2001. The values of ten water quality parameters, such as Temperature, Conductivity, pH, Alkalinity, Free CO2, Salinity, Dissolved Oxygen (DO), Total Suspended Solid (TSS), Hardness and Chemical Oxygen demand (COD) were measured. The values of the parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…but, there was no significant (P > 0.05) variation among the sites and seasons (Figure 3). However, the values of BOD, COD, TDS, and TSS of the Passure River water showed within the range in comparison to the river water quality report of Bangladesh (DoE, 2015) and other mangrove rivers of the world (Toriman et al, 2013;Rahaman et al, 2003;Gandaseca et al, 2016).…”
Section: Water Qualitysupporting
confidence: 62%
“…but, there was no significant (P > 0.05) variation among the sites and seasons (Figure 3). However, the values of BOD, COD, TDS, and TSS of the Passure River water showed within the range in comparison to the river water quality report of Bangladesh (DoE, 2015) and other mangrove rivers of the world (Toriman et al, 2013;Rahaman et al, 2003;Gandaseca et al, 2016).…”
Section: Water Qualitysupporting
confidence: 62%
“…All sites were sampled during day time covering high and low tide. Romesh, 1998APHA, 1992 Water chemistry data from 25 locations between 2001 and 2009 were collected from different sources such as FMRTD (2001), JOECLA (2002), IWM (2003), Rahaman et. al.…”
Section: Methodsmentioning
confidence: 99%
“…However, it remains unclear to what extent this would offset salinity levels . Additionally, past studies found that toxic wastewater release from the neighboring shrimp farms and various industries at Mongla Port have negative impacts on the Sundarbans water quality. , Furthermore, farmers in the area frequently exchange nutrient-enriched water with estuarine waters and dispose toxic farm soil into the surrounding area that eventually ends up in the estuaries and causes eutrophication of the system …”
Section: Water Resourcesmentioning
confidence: 99%